Letter : Basque Children's Trust Limited - Palmer, R. A.
038-0023-001 CO-OPERATIVE UNION LTD. HOLYOAKE HOUSE, HANOVER STREET MANCHESTER 4 General Secretary R.A. PALMER Telegrams - Congress, Manchester Telephone - BLAckfriars 0975 RAP/DPL 27th July, 1942. Mr. H. V. Tewson, Trades Union Congress, Transport House, Smith Square, LONDON, S.W.1. Dear Mr. Tewson, Basque Children's Trust Ltd. I have to acknowledge receipt of your letter of the 23rd July, reference HVT/FC/KA/1744, giving me the information which I requested concerning the above Fund, for which I am much obliged. Yours sincerely, R.A. Palmer 292/946/38/23